TADAKU: Application of Research Questionnaire Collection as an Effort to Increase the Quantity and Quality of Research in Indonesia - Fuji Rahmannisa; Inggo Iwan Kurniawan; Muhammad Fadhli Taqdirul Jabbar; Indira Syawanodya (Journal of Software Engineering, Information and Communication Technology (SEICT), 2021)
Data is crucial in today's modern society. One of the most effective ways to obtain data is through online surveys using online questionnaires. However, there is a lack of online questionnaire creation applications that can motivate respondents to participate in surveys. As a result, survey creators often face difficulties in obtaining responses from respondents. The Tadaku application is designed to address this issue by providing a platform for survey creators to create questionnaires and helping them to reach targeted respondents quickly and accurately by implementing a reward system for participants who are willing to complete the questionnaires. Thus, the Tadaku application provides motivation and benefits for respondents. The questionnaire app system is developed using the waterfall method, which consists of four stages: needs analysis, system design, coding, system testing, and maintenance. The features available in the Tadaku questionnaire application include registration, creating new questionnaires, questionnaire completion, and point redemption for cash rewards.